The challenge of national security, in a heterogeneous state: using Nigeria as a case study - Tonubari Zigha Bornu (The American Journal of Political Science Law and Criminology, 2025)
The issue of national security has always been a determining factor for every government and it has always been an interest that is of topmost priority to every government. The issue of National Security in every political administration cannot be overemphasized, as it is a determining factor in the assessment of a political administration as to whether a government is responsible or not. The government owes every citizen of her state security as to their lives, properties, etc. It is as of right -legal right of the citizens to be protected by their government. Using Nigeria as a case study, if the government is not responsible enough to protect its citizens, economy and other institutions, the Fundamental Rights enlisted under Chapter IV of the Constitution of the Federal Republic of Nigeria 1999 (as amended) can never be in any way attainable, thereby making such government irresponsible. In a heterogeneous state like Nigeria where there are diverse cultures, ethnicities, religions, languages, different sensitivity traits and patterns, etc., the issue of National Security has always been a primary concern. Although of primary significance, it has its challenges amidst it differences, which is what this paper seeks to highlight. This article examines the multifaceted challenges of national security in Nigeria, a nation grappling with a myriad of threats including insurgency, ethnic conflicts, banditry, and organized crime. Historical context reveals how past events, such as civil wars and military coups, have shaped the current security landscape. The rise of Boko Haram and its offshoots, coupled with communal tensions driven by resource scarcity, underscores the complexity of the situation. The government's response, including military interventions and community policing initiatives, is analysed for effectiveness. Additionally, the socio-economic factors contributing to insecurity, such as poverty and youth disenfranchisement, are explored. By evaluating these dynamics, the article underscores the necessity of a holistic approach to national security that integrates economic, social, and political reforms. Ultimately, this case study of Nigeria offers insights relevant to understanding and addressing security challenges in similar contexts globally.